QAR Strategy for Effective Teaching of Reading Comprehension - Nurhayati Nurhayati; Asnawi Muslem; Abdul Manan (Universitas Syiah Kuala, 2019)
The objective of study was to investigate the effect of implementation of Question Aswer Relationship(QAR) strategy on teaching reading comprehension at the third year students of MTsN 7 Aceh Besar.This study employed true experimental in which there were two classes taken as the sample, namely a control group which consisted of 21 students and an experimental group that consisted of 23 students. They were taken through random sampling tehnique. In addition, the data were collected through quantitative (pre-test and post-test) and qualitative method (questionaire). The result shows that the mean of the post-test score of the experimental group was 73.69, while the mean of the post-test scores of control group is 65.64. By comparing t-test score with t-table score, it shows that the result of t-test was 3.08, while the result of t-table at a level of significance with α = 0,05 was 2,021. It means that t-test score is higher than t-table score.The results indicate that alternative hypothesis was accepted and the null hypothesis was rejected. Moreover, the students’ responses toward the use of QAR strategy in learning reading comprehension were quite positive(80.9%). Finally, it can be inferred that QAR strategy is an effective strategy in teaching reading comprehension at the third year students of MTsN 7 Aceh Besar.